Why little Rain over the west and north Arabian Sea and over and around the West Pakistan heat low during the Southwest Monsoon Season ? - DESAI, B. N. (MAUSAM, 1966)
Ramage’s views and model to explain little rain over the west and north Arabian Sea and over and around the West Pakistan heat low have been examined and it is shown that they cannot be accepted. The hitherto prevalent viewpoint about the same is able to explain observations during the IIOE period with a slight modification as suggested by Desai, if one takes into consideration facts of weather, climatology and topography of the Indian subcontinent.